Pengaruh Metode Preview, Question, Read, Reflect, Recite, and Review (PQ4R) terhadap Kemampuan Membaca Pemahaman pada Siswa Kelas IV SDN Kemuningsari Kidul 01 Jember - Fitria Izza Amalina (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Indonesian language learning is one of the subjects that must be mastered by elementary school students. According to the Learning Outcomes Phase B, students are expected to be able to read new words fluently from texts and/or visual media, understand main ideas and supporting ideas, and comprehend messages and information in literary and non-literary texts in printed or electronic forms. However, these learning outcomes are not in accordance with the results of interviews and observations conducted at SDN Kemuningsari Kidul 01, which indicated the presence of reading comprehension problems. Specifically, 64% of students were found to have low reading comprehension ability, such as difficulties in understanding the content of texts, identifying main ideas and supporting ideas, and retelling the content of the reading. These problems were caused by the use of less engaging teaching methods. The purpose of this study was to determine the effect of the Preview, Question, Read, Reflect, Recite, and Review (PQ4R) method on the reading comprehension ability of fourth-grade students at SDN Kemuningsari Kidul 01 Jember. This study employed a pre-experimental research design using a one-group pretest–posttest design. Data were collected through interviews, observations, and documentation. The results of hypothesis testing showed that the Sig. (2-tailed) value was 0.000 < 0.05, leading to the acceptance of H₁ and the rejection of H₀, which indicates a significant difference between students’ pretest and posttest scores. The mean pretest score was 63.48, while the mean posttest score increased to 83.94. Based on these findings, it can be concluded that the Preview, Question, Read, Reflect, Recite, and Review (PQ4R) method has a significant effect on the reading comprehension ability of fourth-grade students at SDN Kemuningsari Kidul 01 Jember.
:: Finalisasi Repositori File 4 Juni 2026_Kurnadi
Keywords: Indonesian Language; Reading Comprehension Ability; PQ4R Method